Decision Analysis of the Composting Unit at Pluit Emplacement, Jakarta Using the Open Bin, Windrow, and Static Pile Methods for Biodegradable Waste - Mega Mutiara Sari; Takanobu Inoue; Regil Kentaurus Harryes; Kuriko Yokota; Iva Yenis Septiariva; Sapta Suhardono; Shigeru Kato; Suprihanto Notodarmojo; Stacia Dea Prameswari; I Wayan Koko Suryawan (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2022)
Indonesian marine debris of aquatic waste in Jakarta is managed by the UPK of the Water Agency, one of which is the Pluit Employment. Several composting methods can be used and adapted to the available circumstances and needs. The composting process is carried out by utilizing the supply of oxygen, nutrients, water, and temperature control. This study aims to analyze the selection of alternative composting systems that can be carried out for planning the composting unit at Pluit Employment. Selection analysis was carried out using the Utility Theory and Compromise program methods. Alternative 1: This alternative uses a composting system using an open bin. Alternative 2 uses a simple windrow system with garbage piled up without heavy equipment during operation. Alternative 3 uses a composting system with a static pile system with a machine turning it over. In the composting method chosen, alternative 2. The distance between compost for workers' movement space, it can reach 1 m as in the TPS 3R Technical instructions, that because it does not use machines, the land used for machine movement is reduced. Limited land can be utilized for the amount of windrow so that the amount of processed waste can be more significant.